(untitled) (Circe de clásicos y modernos, 2018)
To study the role of women in Ancient Greek intellectual landscape means facing the absence of textual evidence of their work, which forces to employ the testimonies of their lives embedded, almost always, in others thinkers’ doxography. This is the case of Aspasia of Miletus, who was part of Pericles’ circle. In this paper I will present a doxographical reconstruction of Aspasia’s activity in the fifth century, bearing in mind the historical situation when she lived and the challenges she faced for being a woman.